COMPARATIVE ASSESSMENT OF THE EFFECT OF GIBBERELLIC AND SALICYLIC ACIDS ON THE GROWTH AND BIOCHEMICAL PARAMETERS OF Phaeodactylum tricornutum - Kovalev, Nikolai Nikolayevich; Leskova, Svetlana Evgenyevna; Mikheev, Evgeny Valerevich (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
The research of the effect of gibberellic (0.4 - 3.8x 10-8 mol.L-1) and salicylic (0.4 - 3.8 x 10-5 mol.L-1) acids, in a wide range of their concentrations, on the growth indicators and biochemical composition of the cumulative culture of the microalgae Phaeodactylum tricornutum was carried out. It was determined that salicylic acid in a concentration of 0.4 x 10-5 mol stimulated cell growth by 184.6%, and gibberellic acid at a concentration of 0.39 x 10-8 mol by 181%, compared to the control. The effect of gibberellic acid during the experiment was expressed in the inhibition of protein accumulation in the culture, compared with the control. The use of salicylic acid led to a greater accumulation of protein in the culture than when using gibberellic acid. It was shown that salicylic acid had a positive effect on the accumulation of carbohydrates on day 9 and gibberellic acid on day 14 of culture. Gibberellic acid had no effect on the accumulation of lipids in the culture of microalgae. Under the action of salicylic acid for 14 days of cultivation, the lipid content increased by 18.5%, compared with the control. There were no quantitative differences in the content of chlorophyll when using two phytohormones. In this study, the optimal concentrations of gibberellic and salicylic acids for linear growth rate and the highest production of protein and carbohydrates for Phaeodactylum tricornutum were determined. Position, depending on the stage of microalgae growth, is noted.